THE ROLE OF LITERATURE IN INDONESIAN DEVELOPMENT PROCESS - Wati, Erna (CaLLs (Journal of Culture, Arts, Literature, and Linguistics), 2016)
In Indonesia, literature has been one of critical media to respond to the political and social issues. This study reviewed three literary works of the three Indonesian writers from different era: Bumi Manusia (1980) by Pramoedya Ananta Toer, Potret Pembangunan dalam Puisi (1980) by W.S. Rendra and Laskar Pelangi (2008) by Andrea Hirata. In this study, the writer analyzed how each literary work conceive the idea of political and educational development and how they contribute positive impacts to the development process of Indonesia society. The findings confirm each literary work has some similarities to the other in regards to contribute the idea of Indonesia development. The three authors agreed that education is an effective aspect to develop Indonesia society. They also have the same opinion that education which has a better quality is not always come from the formal institution. They depict a wider concept of education which is obtained from the fantastic culture and moral values.Keywords: Indonesian literature, the role of literature, development